Early detection of breast cancer rectifies inequality of breast cancer outcomes. (March 2021) - Tabár, László; Chen, Tony Hsiu-Hsi; Yen, Amy Ming-Fang; Dean, Peter B; Smith, Robert A; Jonsson, Håkan; Törnberg, Sven; Chen, Sam Li-Sheng; Chiu, Sherry Yueh-Hsia; Fann, Jean Ching-Yuan; Ku, May Mei-Sheng; Wu, Wendy Yi-Ying; et al.
Objectives: To explain apparent differences among mammography screening services in Sweden using individual data on participation in screening and with breast cancer–specific survival as an outcome. Methods: We analysed breast cancer survival data from the Swedish Cancer Register on breast cancer cases from nine Swedish counties diagnosed in women eligible for screening. Data were available on 38, 278 breast cancers diagnosed and 4312 breast cancer deaths. Survival to death from breast cancer was estimated using the Kaplan–Meier estimate, for all cases in each county, and separately for cases of women participating and not participating in their last invitation to screening. Formal statistical comparisons of survival were made using proportional hazards regression. Results: All counties showed a reduction in the hazard of breast cancer death with participation in screening, but the reductions for individual counties varied substantially, ranging from 51% (95% confidence interval 46–55%) to 81% (95% confidence interval 74–85%). Survival rates in nonparticipating women ranged from 53% (95% confidence interval 40–65%) to 74% (95% confidence interval 72–77%), while the corresponding survival in women participating in screening varied from 80% (95% confidence interval 77–84%) to 86% (95% confidence interval 83–88%), a considerably narrower range. Conclusions: Differences among counties in the effect of screening on breast cancer outcomes were mainly due to variation in survival in women not participating in screening. Screening conferred similarly high survival rates in all counties. This indicates that the performance of screening services was similar across counties and that detection and treatment of breast cancer in early-stage reduces inequalities in breast cancer outcome.